Factors Affecting The Disclosure Of Social Information In Annual Reports On Listed Manufacturing Companies On The Indonesia Stock Exchange (Idx) - Catrin Valentina Sihombing (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2023)
This study aims to determine the effect of profitability, board size, leverage and firm size on CSR disclosure in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The sampling method used in this research is purposive sampling method. The number of samples in this study were 18 companies. The data analysis method used is multiple linear regression analysis. The results of the study partially show that the profitability variable (ROA) has no significant effect on CSR disclosure with a significant value of 0.928 > 0.05, so the first hypothesis is rejected. The variable size of the board of commissioners has a significant effect on CSR disclosure with a significant value of 0.002 <0.05, so the second hypothesis is accepted. The leverage variable (DAR) has no significant effect on CSR disclosure with a significant value of 0.604 > 0.05, so the third hypothesis is rejected. Firm size variable has a significant effect on CSR disclosure with a significant value of 0.004 <0.05, so the fourth hypothesis is accepted. The results of the model suitability test showed that the profitability (ROA), board size, leverage (DAR) and firm size had a significant effect on CSR disclosure with a significant value of 0.003 <0.05. In the analysis of the coefficient of determination obtained a value of 0.277 or 27.7% and the remaining 79.6% is influenced outside the model tested in this study.